Investigation of Thermal Annealing Condition on the Optical and Electrical Properties of Hybrid Silver Nanowires/Reduced Graphene Oxide (AgNWS/rGO) Films - Thu, Hoang Thi; Hoa, Huynh Tran My; Phuong, Pham Hoai; Nhu, Nguyen Huynh; Trung, Tran Quang; Long, Lam Minh; Dinh, Nguyen Nang (Communications in Physics, 2014)
Herein we report a electrode in the hybrid structure of the silver nanowires (AgNWs) with reduced graphene oxide (rGO) deposited on glass or PET substrate. The assembly and contacting in procedures of this hybrid film have been strongly affected by preparation conditions, especially annealing temperature. In this work, we have investigated the effects of thermal annealing on interconnected at nanowire junctions and between AgNWS network and rGO films via their sheet resistance and transmission. The annealing temperature was varied from 120\(^°\)C to 180\(^°\)C with 10\(^°\)C step to find out optimal temperature at which the wires can be joined together. The results show that at 170\(^°\)C, the sheet resistance and transmission of the hybrid rGO/Ag NW film are \(R_s = 10.7 Ω\) sq\(^ - 1 \) and \(T = 77\)% (at wavelength 550 nm) corresponding to the ratio of direct conductivity to optical conductivity \(σ _DC/σ _OP = 126\) which is the best obtained value. It is expected that the hybrid AgNWS/rGO film can replace ITO film in the near future.